2019
DOI: 10.1002/pssa.201900512
|View full text |Cite
|
Sign up to set email alerts
|

Growth of InGaAs Solar Cells on InP(001) Miscut Substrates Using Solid‐Source Molecular Beam Epitaxy

Abstract: Herein, the effects of both the growth temperature and the substrate miscut on the properties of lattice‐matched InGaAs solar cells grown on InP substrates via solid‐source molecular beam epitaxy are investigated. The growth temperature is varied from 420 to 490 °C. InP(001) miscut by 2° toward (111)A and (111)B denoted by 2°A and 2°B, respectively, and exactly‐cut substrates are used. Material quality is evaluated by photoluminescence (PL) and atomic force microscopy (AFM) measurements. At room temperature, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…For instance, the 3-junction lattice mismatched solar cell can be extended to a 4-junction or more junction on GaAs substrate by adding another lattice mismatched Ga x In 1−x As junction. The In x Ga 1−x As heteroepitaxial growth on GaAs substrate has been applied to many terrestrial and space energy conversion applications for the following reasons: (i) the ternary In x Ga 1−x As semiconductor with varied bandgap energy from 0.36 to 1.42 eV is suitable for the most optic-electronic devices [8], such as thermophotovoltaic [9], III-V semiconductor solar cells [10] and lasers [11]; (ii) the carries mobility of In x Ga 1−x As material is high, which can be applied in high speed electronic devices [12]. Recently, A metamorphic Al 0.18 Ga 0.33 In 0.49 P/Al 0.23 Ga 0.77 As/Ga-As/Ga 0.66 In 0.34 As/Ga 0.42 In 0.58 As 6-junction solar cell by NREL [13] have demonstrated AM1.5 143-suns efficiencies in exceed of 47.1%, The 6-J solar cell is proposed to match the solar spectrum and balance the photocurrent generated from each subcell, of which Ga 0.66 In 0.34 As and Ga 0.42 In 0.58 As subcells are lattice-mismatched to GaAs substrate.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the 3-junction lattice mismatched solar cell can be extended to a 4-junction or more junction on GaAs substrate by adding another lattice mismatched Ga x In 1−x As junction. The In x Ga 1−x As heteroepitaxial growth on GaAs substrate has been applied to many terrestrial and space energy conversion applications for the following reasons: (i) the ternary In x Ga 1−x As semiconductor with varied bandgap energy from 0.36 to 1.42 eV is suitable for the most optic-electronic devices [8], such as thermophotovoltaic [9], III-V semiconductor solar cells [10] and lasers [11]; (ii) the carries mobility of In x Ga 1−x As material is high, which can be applied in high speed electronic devices [12]. Recently, A metamorphic Al 0.18 Ga 0.33 In 0.49 P/Al 0.23 Ga 0.77 As/Ga-As/Ga 0.66 In 0.34 As/Ga 0.42 In 0.58 As 6-junction solar cell by NREL [13] have demonstrated AM1.5 143-suns efficiencies in exceed of 47.1%, The 6-J solar cell is proposed to match the solar spectrum and balance the photocurrent generated from each subcell, of which Ga 0.66 In 0.34 As and Ga 0.42 In 0.58 As subcells are lattice-mismatched to GaAs substrate.…”
Section: Introductionmentioning
confidence: 99%
“…We also calculated the bandgap-voltage offset, W oc (=E g /q − V oc ), 5,19,20) of the cell used in this study and obtained 0.454 V. For latticematched 0.74 eV InGaAs solar cells, lower W oc values of 0.34 and 0.369 V have been reported. 19,20) Lattice-mismatched InGaAs solar cells have shown voltage losses of about 0.38 V compared to their bandgap energies and in these devices threading dislocation densities were about 2 × 10 6 cm −2 . 5) These W oc values are below 0.4 V, which is the range of values achieved by solar cells with a high material quality solar cell.…”
mentioning
confidence: 96%
“…From the I-V curves of these samples, we found that the bandgap-voltage offset W oc (=E g /q − V oc ) 34,35) values for samples A and B are 0.585 V and 0.438 V, respectively. The W oc value reflects the crystal quality of a junction, and high-quality IMM1J InGaAs solar cells have a W oc below 0.4 V. 35) Therefore, sample A has a significantly poorer crystal quality than the high-quality devices reported previously.…”
mentioning
confidence: 96%